Proceedings of the 12th International Conference on Business and Management Research (ICBMR 2018) 2019
DOI: 10.2991/icbmr-18.2019.34
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence the Attitude and Behavioral Intention of Indonesian Users toward Online Food Delivery Service by the Go-Food Application

Abstract: The internet as one of the medias that grows fast in Indonesia makes the people of Indonesia have a tendency to do various activities through internet facilities and other supporting applications. Some Indonesians prefer to use an online shop because it provides better convenience motivation and economic value than traditional shopping. This also occurs in the food and beverage sector, which encourages the emergence of online food delivery services or OFD services. This study aims to examine the influence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 13 publications
(30 reference statements)
4
40
0
7
Order By: Relevance
“…Customer perceptions toward OFDS can be measured by how much money they can save by using it. The more money a customer saves, or the lower the price that the customers pays, the more the customer tends to perceive that a related service is convenient to use [9]. Interestingly, SEM revealed that price has the second-largest effect after HM on the model framework.…”
Section: Discussion: Customer Satisfaction About Food Delivery In Thementioning
confidence: 95%
See 4 more Smart Citations
“…Customer perceptions toward OFDS can be measured by how much money they can save by using it. The more money a customer saves, or the lower the price that the customers pays, the more the customer tends to perceive that a related service is convenient to use [9]. Interestingly, SEM revealed that price has the second-largest effect after HM on the model framework.…”
Section: Discussion: Customer Satisfaction About Food Delivery In Thementioning
confidence: 95%
“…Instead, customers make a purchase in order to fulfill a pleasure, and it is heavily influenced by the surroundings in which the user is in. Moreover, HM strongly affects emotional arousal, which triggers customers to make a purchase [9]. The respondents mostly felt that they utilized OFDS, not only for fulfilling the basic needs, but also as an enjoyable platform for buying food for someone else.…”
Section: Discussion: Customer Satisfaction About Food Delivery In Thementioning
confidence: 99%
See 3 more Smart Citations